2015
DOI: 10.1016/j.pmrj.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐rater Reliability of Real‐Time Ultrasound to Measure Acromiohumeral Distance

Abstract: RTUS was found to have fair to good inter-rater reliability as a tool to measure acromiohumeral distance with the shoulder in a neutral position and with 60° of both active and passive arm abduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…[28][29][30] reported similar degrees of reliability for both measurements, although dynamic evaluation presents another issue with acromiohumeral distance measurements. Mackenzie et al 20 reported ICC scores that were fair to good for inter-rater reliability of acromiohumeral distance measurements in all three of the shoulder positions tested (neutral, 0.88; passive arm abduction, 0.65; active arm abduction, 0.68). Desmeules et al 14 observed a more pronounced dynamic narrowing during abduction from 0° to 45°, which might indicate that the shorter acromiohumeral distance in shoulder impingement syndrome patients could be due to increased superior translation of the humeral head caused by rotator cuff failure or pain inhibition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[28][29][30] reported similar degrees of reliability for both measurements, although dynamic evaluation presents another issue with acromiohumeral distance measurements. Mackenzie et al 20 reported ICC scores that were fair to good for inter-rater reliability of acromiohumeral distance measurements in all three of the shoulder positions tested (neutral, 0.88; passive arm abduction, 0.65; active arm abduction, 0.68). Desmeules et al 14 observed a more pronounced dynamic narrowing during abduction from 0° to 45°, which might indicate that the shorter acromiohumeral distance in shoulder impingement syndrome patients could be due to increased superior translation of the humeral head caused by rotator cuff failure or pain inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…It was revealed that a random sample of 100 subjects, each measured twice, produced a two-sided 95% confidence interval (CI) with width of 0.200 when the estimated intraclass correlation is 0.700 using a one-way random-effects analysis of variance model. 20 A 5-10-mHz linear probe was used in B mode (Mindray Medical International Co., Ltd., Shenzhen, China). The supraspinatus tendon thickness, acromiohumeral distance, and occupation ratio were measured by two observers with at least two years of experience using musculoskeletal ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, during the pre-intervention ultrasound exam, three images of the AHD were taken during 90˚ elbow flexion with the thumb facing upwards, as has been done previously and proven good reliability ( Figure 2). 21 Self-reported subject characteristics: Participants were asked to self-report sociodemographic variables (age, sex, and height), characteristics of the injury (traumatic or nontraumatic etiology, date of injury, completeness of the injury, and neurological lesion level), medication intake due to pain in the upper extremities in the last three months, and the 13item Physical Activity Scale for Individuals with Physical Disabilities (PASIPD). The PASIPD has good construct validity and test-retest reliability.…”
Section: Data Collectionmentioning
confidence: 99%
“…Participants were seated upright, and the upper limb was positioned on a pillow placed on their lap, the shoulder in 608 of abduction; the elbow in 908 of flexion by using a goniometer, and the hand in neutral with the thumb pointing upward. We measured AHD at 608 of shoulder abduction, as acoustic shadows might occur in higher ranges of shoulder abduction, 26,27 and US measurement of AHD at 608 of shoulder abduction has shown excellent reliability in asymptomatic individuals 27 and patients with subacromial impingement syndrome. 28 The transducer was placed on the lateral surface of the acromion in the coronal plane and was parallel with the long axis of the humerus, where the shortest distance between the humerus and acromion was observed.…”
Section: Data Collectionmentioning
confidence: 99%
“…The measurements were repeated 3 times, and the mean value was calculated. Researchers 26,27,29,30 have shown good interrater and intrarater reliability in the US measurement of AHD in healthy individuals.…”
Section: Data Collectionmentioning
confidence: 99%